Strengthening ASEAN’s Stabilizing Role via ASEAN Outlook on the Indo-Pacific - Paramitha, Devy Indah; Syabana, Muhammad Nur Alim; Amin, Khoirul (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2025)
The Indo-Pacific has become at the forefront of geostrategic rivalry between the United States and China, which has implications for region’s political, security and economic stability. As the only regional institution with multilateral capacity in the Indo-Pacific, ASEAN faces the challenge of maintaining its neutrality while strengthening its centrality. This context explains how, through the 2019 ASEAN Outlook on the Indo-Pacific (AOIP), ASEAN seeks to reinforce its stabilizing role by adopting preventive, mitigative, and adaptive strategies in response to regional power shifts. Using a descriptive qualitative method and the statement of strategy concept contextualized with neorealism, this study analyses the AOIP is an ASEAN’s strategic response to regional power competition between the great powers. The finding shows that AOIP, as neutral framework, aims to foster cooperation in various sectors, including industry. ASEAN's neutrality is also tested in policymaking, particularly among Southeast Asia members, as it strives to manage tension between major powers while maintaining its coherence, relevance and influence in the evolving Indo Pacific order.